THE CORRELATION BETWEEN THE FIRST-YEAR STUDENTS’ VOCABULARY MASTERY AND WRITING DESCRIPTIVE TEXT ABILITY AT SMPN 1 TEBING TINGGI - Fita Maghvira; Eliwarti; Muhammad Syarfi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the correlation between two variables, namely vocabulary mastery and writing descriptive text ability of the first-year students at SMPN 1 Tebing Tinggi. The researcher used a quantitative research method as the data approach. The population consisted of the first-year students with a total of 124 students. The researcher used a simple random sampling technique and selected 32 students from all classes. The instruments used were two types of tests: multiple-choice tests and written tests. To analyze the data, the researcher used SPSS Statistics 25. The research results indicate that the first-year students of SMPN 1 Tebing Tinggi achieved a good level of vocabulary mastery and a mediocre level of writing descriptive text ability. The results also indicate that there is a correlation between vocabulary mastery and writing descriptive text ability. The Rxy distribution of the coefficient correlation was 0.408. This means that there was a correlation between vocabulary mastery and writing descriptive text ability of the first-year students at SMPN 1 Tebing Tinggi at a fair level. Thus, the null hypothesis (Ho) was rejected and the alternative hypothesis (Hα) was accepted.